The Pathogenic Effects of Fusobacterium nucleatum on the Proliferation, Osteogenic Differentiation, and Transcriptome of Osteoblasts - Gao, Hui; Sun, Tianyong; Yang, Fanghong; Yuan, Jiakan; Yang, Mei; Kang, Wenyan; Tang, Di; Zhang, Jun; Feng, Qiang (Frontiers in Cell and Developmental Biology, 2020)
As one of the most common oral disease, periodontitis is closely correlated with tooth loss in middle-aged and elderly people. Fusobacterium nucleatum (F. nucleatum) contributes to periodontitis, but the evidence in alveolar bone loss is still unclear. In this study, cytological experiments and transcriptome analysis were performed to characterize the biological process abnormalities and the molecular changes of F. nucleatum-stimulated osteoblasts. F. nucleatum could inhibit cell proliferation, promote cell apoptosis, and elevate pro-inflammatory cytokine production of osteoblasts, and it also inhibited osteoblast differentiation and mineralized nodules formation and decreased the expression of osteogenetic genes and proteins. Whole-transcriptome analysis identified a total of 235 transcripts that were differentially expressed in all six time-points, most of which were inflammatory-related genes. The genes, Ccl2, Ccl20, Csf1, Cx3cl1, Cxcl1, Cxcl3, Il6, Birc3, Map3k8, Nos2, Nfkb2, Tnfrsf1b and Vcam1, played core roles in a PPI network and interacted closely with other ones in the infection. In addition, 133 osteogenesis-related DEGs were time-serially dynamically changed in a short time-series expression miner (STEM) analysis, which were enriched in multiple cancer-related pathways. The core dynamic DEGs (Mnda, Cyp1b1, Comp, Phex, Mmp3, Tnfrsf1b, Fbln5 and Nfkb2) had been reported to be closely related to the development and metastasis in tumor and cancer progress. This study is the first to evaluate the long-term interaction of F. nucleatum on osteoblasts, which might increase the risk of cell carcinogenesis of normal osteoblasts, and provides new insight into the pathogenesis of bacterial-induced bone destruction.